Plant Growth‐Promoting Rhizobacteria (PGPR) Reduce Evaporation and Increase Soil Water Retention. Issue 5 (22nd May 2018) - Zheng, Wenjuan; Zeng, Saiqi; Bais, Harsh; LaManna, Jacob M.; Hussey, Daniel S.; Jacobson, David L.; Jin, Yan
Abstract: Enhancement of plant drought stress tolerance by plant growth‐promoting rhizobacteria (PGPR) has been increasingly documented in the literature. However, most studies to date have focused on PGPR‐root/plant interactions; very little is known about PGPR's role in mediating physiochemical and hydrological changes in the rhizospheric soil that may impact plant drought stress tolerance. Our study aimed to advance mechanistic understanding of PGPR‐mediated biophysical changes in the rhizospheric soil that may contribute to plant drought stress tolerance in addition to plant responses. We measured soil water retention characteristics, hydraulic conductivity, and water evaporation in soils with various textures (i.e., pure sand, sandy soil, and clay) as influenced by a representative PGPR ( Bacillus subtilis strain UD1022) using the HYPROP system. We found that all PGPR‐treated soils held more water and had reduced hydraulic conductivity and accumulative evaporation, compared to their corresponding controls. We discuss three mechanisms, due to B. subtilis incubation or production of extracellular polymeric substances (EPS), that are potentially responsible for the changes in hydraulic properties and soil evaporation: (i) EPS have a large water holding capacity; (ii) EPS alter soil matrix structure and connectivity of pore space; (iii) EPS modify the physicochemical properties of water (surface tension and viscosity). These results clearly demonstrate PGPR's ability to increase water availability to plants by slowing down evaporation and by increasing the time available for plants to make metabolic adjustments to drought stress. Plain Language Summary: PGPR is a group of beneficial bacteria known to improve plant growth by, e.g., reducing pathogenic infection and/or promoting drought/salt tolerance. Despite the important role PGPR could potentially play in reducing drought stress to plants, we lack a complete understanding on the mechanisms through which PGPR mediate plant tolerance to drought. This study aimed to advance mechanistic understanding of PGPR‐mediated biophysical changes in soil through microbe‐soil interactions, to complement better understanding gained from previous studies that focused on microbe‐plant interactions. Through laboratory measurements and imaging of water retention in soil, we show that a representative PGPR ( B. subtilis UD1022) can increase soil water retention and reduce soil water evaporation. This effect is likely caused by the PGPR's ability to produce extracellular polymeric substances, which have high water holding capacity and can induce changes in soil physical properties. These changes lead to slower evaporation from soil, which can make more water available to plants as well as increase the time available for plants to make metabolic adjustments to drought stress. Our results provide scientific support to recent efforts in promoting application of rhizobacteria isolates as "underground resource" to contribute to solving globally challenging issues, e.g., water resource shortage and food security. Key Points: Improved soil water holding capacity and reduced soil water evaporation were found for PGPR‐treated soil samples EPS production was responsible for the changes in the observed hydraulic properties Findings imply PGPR increase water availability, slow down the drying processes, and relieve the stress experienced by roots upon drought